Clinical utility of the Therapeutic Intervention Scoring System (TISS-28) as a predictor of mortality in critically ill patients: A retrospective study in an Intensive Care Unit in Montería, Colombia: Utilidad clínica del Sistema de Puntuación de Intervenciones Terapéuticas (TISS-28) como predictor de mortalidad en pacientes críticos: estudio retrospectivo en una Unidad de Cuidados Intensivos de Montería, Colombia - Ortiz-Girón, José María; Bustos Gonzalez, Álvaro; Diaz Cornejo, Nora; Ortiz Diaz, Daniel José; Ortiz Diaz, Carlos Saúl; Ruiz Garces, Luis (Gaceta Médica de Caracas, 2025)
Introduction: The care of critically ill patients represents multiple clinical and organizational challenges. Mortality in the Intensive Care Unit (ICU), influenced by patient severity and interventions performed, is a key indicator of hospital performance. Objective: This study aimed to evaluate the clinical utility of the Therapeutic Intervention Scoring System (TISS-28) as a predictor of mortality in a tertiary ICU in Montería, during the period 2019-2023. Methods: A descriptive, retrospective study with a quantitative approach. Patients with complete TISS-28 score records were included in the analysis.